1999
DOI: 10.1021/es9807035
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Organic Aerosol Formation vs Primary Organic Aerosol Emission:  In Situ Evidence for the Chemical Coupling between Monoterpene Acidic Photooxidation Products and New Particle Formation over Forests

Abstract: In a Eucalyptus forest in Portugal were investigated (a) the formation of secondary organic aerosol formed through the condensation of low vapor pressure products of monoterpenes (α- and β-pinene) photooxidation and (b) the chemical structure of these products related to their ability to form new particles. Two isomers of pinonic acid (cis- and trans-2,2-dimethyl-3-acetylcyclobutylethanoic acid) and norpinonic acid (cis- and trans-2,2-dimethyl-3-acetylcyclobutylmethanoic acid), pinic acid (cis-2,2-dimethyl-3-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 32 publications
4
93
1
5
Order By: Relevance
“…These species have been used to evaluate the role of monoterpene oxidation in the formation of SOA (Kavouras et al, 1999;Miyazaki et al, 2012). Monoterpenes account for 35 % of the global emissions of biogenic VOCs (Griffin et al, 1999).…”
Section: P Q Fu Et Al: Aircraft Measurements Of Polar Organic Tracmentioning
confidence: 99%
“…These species have been used to evaluate the role of monoterpene oxidation in the formation of SOA (Kavouras et al, 1999;Miyazaki et al, 2012). Monoterpenes account for 35 % of the global emissions of biogenic VOCs (Griffin et al, 1999).…”
Section: P Q Fu Et Al: Aircraft Measurements Of Polar Organic Tracmentioning
confidence: 99%
“…Aerosol organic carbon in forests is believed to be dominated by biogenic SOA, especially in summer when biological activities are maximized under intense sunlight and high ambient temperature conditions. However, studies on time-resolved diurnal variations of ambient SOA at a molecular level in the forest atmosphere are limited (Kavouras et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic acids, particularly phthalic acid, have been thought to be secondary products of the oxidation of PAH, including naphthalene (Fraser et al 2003, Jang andMcDow 1997), while origins proposed for aliphatic dicarboxylic acids comprise the formation by photochemical oxidation of anthropogenic hydrocarbons and biogenic compounds, direct emission from combustion engines, or biomass combustion (Kubátová et al 2000 and references therein). Although dicarboxylic acids can be of primary or secondary origin, several studies have revealed contributions to SOA by dicarboxylic acids formed in situ during atmospheric aerosol processing (Glassius et al 2000, Kavouras et al 1998b, 1999c, Kawamura et al 1996. The dicarboxylic acids measured by Engling et al (2006) during the summer of 2002 in Yosemite National Park (CA, USA) showed a relatively large variability in concentrations throughout the study based on the weekly composite samples (1.3-11 ng m −3 for the sum of C 4 through C 14 dicarboxylic acids).…”
Section: An Acad Bras Ciencmentioning
confidence: 98%
“…The formation of nopinone may also take place after oxidation of β-pinene by NO x (Grosjean et al 1992, Paulson et al 1990, O 3 /NO x (Palen et al 1992) or NO x /SO 2 (Kotzias et al 1990). (2008) Although monoterpenes are an important source of biogenic organic aerosols (Kavouras et al 1999c, Hoppel et al 2001, we still have missing sources that contributes to secondary organic aerosols of biological origin. Matsunaga et al (2003) measured, in both gas and particle phases, glycolaldehyde and hydroxyacetone which are known as the oxidation products of isoprene (Atkinson 1990), together with biogenic semi-volatile aldehydes (n-nonanal and n-decanal; Kesselmeier and Staudt 1999).…”
Section: Oxidation Products Of Vocmentioning
confidence: 99%